The Role of the Police Civil Servant Unit in Handling LGBT Cases in Bukittinggi City - Yusra Dila Maiza; Riki Zulfiko (Fakultas Hukum Universitas Djuanda, 2025)
Bukittinggi as a tourist city is inseparable from a social phenomenon, one of the phenomena is LGBT, according to the philosophy of